Additions to the Flora of Telangana state of India, with notes on the phytogeographical importance. Issue 2 (24th October 2021) - Gollamandala, Ravi; Parappurakkal Thazhe, Arunraj; Lingala, Paramesh; Paradesi, Anjaneyulu; Dasari, Veeranjaneyulu
Abstract: The recent floristic explorations in Bhadradri Kothagudem district yielded three flowering plants as additions to the flora of Telangana state. These additions include new record of one family Rhizophoraceae Pers., represented by Carallia brachiata (Lour.) Merr. and two species records from the family Linderniaceae Borsch, Kai Müll. & Eb.Fisch. viz. Torenia godefroyi Bonati and Lindernia rotundifolia (L.) Alston. Detailed morphological description, distribution, habitat and ecology, and photographs of each species are provided. A brief account on the phytogeographical importance of the present additions is given.